Розробка конструкції корпусу 3d принтеру з механікою Delta - Олійник, А.; Баданюк, І.; Іорданов С. (ХНУРЕ, 2019)
Nowadays, 3D printers do not cease to be modified, today there is not enough of their number of different shapes and dimensions, which makes the development of 3D printing relevant and applied in nature. Particular attention deserves 3D printers with kinematics Delta. This kinematics appeared not so long ago, but despite this, it has great prospects. 3D printers with Delta kinematics differ from other printers by case design. It will not be possible, from the one on which the precisionly assembled body corresponds to the accuracy of the print, also if it is not rigid during printing.
Keywords: 3D принтер; Delta